Estratégias de controle para suporte dinâmico de tensão durante faltas em smart inverters utilizados na geração fotovoltaica conectada à rede de distribuição - Santos, Rafaella Aparecida Franco (2022)
The interconnection of Distributed Generation (DG) systems to the electrical grid, mainly with renewable energy sources, has grown rapidly in recent years. Among the renewable sources of DG, the most common currently used is solar photovoltaics. However, the increase in the number of DGs in the electrical system also causes impacts, making it necessary to update the rules that regulate the interconnection of these systems to the grid. This work explores the Volt-VAr control for voltage support during faults through a dynamic analysis of a photovoltaic system connected to the distribution network. For this, a 50 kW photovoltaic system was modeled with the aid of Simulink block diagram resources, and the MATLAB software was used to generate the initialization algorithm for the system simulation. The proposed Volt-Var control considers different techniques for prioritizing the use of the inverter current capacity together with strategies for additional control of the DC link voltage. The first simulations had the purpose of evaluating the performance of the Volt-VAr control during faults in view of the interaction between the different techniques of prioritization of the use of the current capacity of the inverter for injection of active or reactive current with the three strategies for voltage control of the DC link, named: Constant Active Power, Constant Active Current and Constant Current Peak. Subsequently, the Constant Active Current strategy with prioritization of the active current component of the inverter was selected and evaluated against the variation of the system operating point and different fault intensities, including the case in which the inverter current does not suffer saturation, allowing the reactive current get more room to grow. The studies showed that the network used has a resistive characteristic, resulting in a low influence of the reactive power on the voltage in relation to the active power, reducing the effectiveness of the Volt-Var control. Finally, the network characteristics (X/R ratio) were varied to verify their influence on the performance of the Volt-VAR control. The results showed that, for a more inductive network, the Volt-VAr control was effective in supporting the terminal voltage during a fault.